Engineering boron-imidazolate-based polyoxometalates for photooxidative C=C bond cleavage in aqueous media - Jiajia Wang; Zhaoyang Wu; Qun Li; Hanlei Zhang; Yang Liu; Guixiao Ji; Yalin Zhang; Qianli Li; Junyu Ren; Qingde Zhang; Xianqiang Huang (Polyoxometalates, 2025)
The direct cleavage of alkenes to access value-added carbonyls under solar-driven conditions in aqueous media presents a considerable challenge. Addressing this challenge requires the construction of effective visible-light-responsive catalysts. Herein, two boron-imidazolate-based Strandberg-type polyoxomolybdophosphate hybrids, Co(H2O)4[HP2Mo5O23]2[B(HIM)(IM)2]2[B(HIM)3]2·12H2O (1) and Zn(H2O)4[HP2Mo5O23]2[B(HIM)(H2IM)2]4·7H2O (2) (IM = imidazole), were synthesized using a hydrothermal method and were utilized as efficient photocatalysts for the aerobic oxidative C=C bond cleavage of alkenes under natural sunlight and aqueous phase conditions. The incorporation of boron imidazolate ligands broadened the visible-light absorption region of polyoxometalates, and electrochemical tests highlighted their potential as exceptional photocatalysts. Upon visible blue light irradiation and ambient O2 pressure in aqueous media, compound 1 exhibited remarkable aerobic photocatalytic activity, efficiently cleaving alkenes to yield the corresponding ketones (yields up to 91%). Notably, its catalytic performance remained consistent after three recycling runs under ambient sunlight, highlighting its robust stability and practical applicability. Subsequent mechanistic investigations revealed the involvement of O2•− species in the reaction, and a possible mechanism for the cleavage of the alkenes was proposed.